"Technical" Contributors and Authorship Distribution in Health Science. - Smith, Elise (Science & Engineering Ethics, 2023)
In health sciences, technical contributions may be undervalued and excluded in the author byline. In this paper, I demonstrate how authorship is a historical construct which perpetuates systemic injustices including technical undervaluation. I make use of Pierre Bourdieu's conceptual work to demonstrate how the power dynamics at play in academia make it very challenging to change the habitual state or "habitus". To counter this, I argue that we must reconceive technical contributions to not be a priori less important based on its nature when assigning roles and opportunities leading to authorship. I make this argument based on two premises. First, science has evolved due to major information and biotechnological innovation; this requires 'technicians' to acquire and exercise a commensurate high degree of both technical and intellectual expertise which in turn increases the value of their contribution. I will illustrate this by providing a brief historical view of work statisticians, computer programmers/data scientists and laboratory technicians. Second, excluding or undervaluing this type of work is contrary to norms of responsibility, fairness and trustworthiness of the individual researchers and of teams in science. Although such norms are continuously tested because of power dynamics, their importance is central to ethical authorship practice and research integrity. While it may be argued that detailed disclosure of contributions (known as contributorship) increases accountability by clearly identifying who did what in the publication, I contend that this may unintentionally legitimize undervaluation of technical roles and may decrease integrity of science. Finally, this paper offers recommendations to promote ethical inclusion of technical contributors.